Electrophysiological evidence for the action of a center-surround mechanism on semantic processing in the left hemisphere - Deacon, Diana; Shelley-Tremblay, John F.; Ritter, Walter; Dynowska, Anna (Frontiers in Psychology, 2013)
Physiological evidence was sought for a center-surround attentional mechanism (CSM), which has been proposed to assist in the retrieval of weakly activated items from semantic memory. The CSM operates by facilitating strongly related items in the “center” of the weakly activated area of semantic memory, and inhibiting less strongly related items in its “surround”. In this study weak activation was created by having subjects acquire the meanings of new words to a recall criterion of only 50%. Subjects who attained this approximate criterion level of performance were subsequently included in a semantic priming task, during which ERPs were recorded. Primes were newly learned rare words, and targets were either synonyms, nonsynonymously related words, or unrelated words. All stimuli were presented to the RVF/LH (right visual field/left hemisphere) or the LVF/RH (left visual field/right hemisphere). Under RVF/LH stimulation the newly learned word primes produced facilitation on N400 for synonym targets, and inhibition for related targets. No differences were observed under LVF/RH stimulation. The LH thus, supports a CSM, whereby a synonym in the “center” of attention focused on the newly learned word is facilitated, whereas a related word in the “surround” is inhibited. The data are consistent with the view of this laboratory that semantic memory is subserved by a spreading activation system in the LH. Also consistent with our view, there was no evidence of spreading activation in the RH. The findings are discussed in the context of additional recent theories of semantic memory. Finally, the adult right hemisphere may require more learning than the LH in order to demonstrate evidence of meaning acquisition.